Dukusu Rangeland Unit: Participatory Rangeland Management Plan - Dukusu Rangeland Community (International Livestock Research Institute, 2024)
This is the rangeland management plan produced by the Dukusu rangeland community, under participatory rangeland management (PRM), as part of a One Health approach supported by the project HEAL.